A Study of Occupational Stress on Doctors during Covid 19 Pandemic with Reference to North West Delhi (International Journal of Innovative Research in Engineering & Management, 2021)
This research paper aims to assess the occupational stress among  professional physicians whereas engaging the COVID-19  therapies in the research location. The Coronavirus pandemic in  India is part of a worldwide pandemic caused by the brutally acute  pulmonary syndrome virus. Physicians and the general public  have expressed concern, grief, fear, and sadness as a result of the  COVID-19 eruption. Doctors are more likely then the general  population to suffer from a variety of mental diseases. All main  and tertiary data were used in the inquiry. Secondary data was  gathered on COVID-19 diseases and physician treatments. The  important information obtained from clinicians relates to the  COVID-19 treatment. The study has a sample size of 353. The  responses were compiled into excel sheets, which were then  imported into SPSS program versions 21 for analysis. For  evaluating the framed hypothesis, the researchers used simple  statistical distribution and a t-test. According to the study, the  doctors used COVID-19 treatment for the initial 6 weeks, and %  of the professionals had high stress levels. The study also found  that when government hospital doctors started using COVID-19  therapy in hospitals, their work culture altered dramatically.  According to the poll, government hospital doctors were unable  to maintain a work-life balance. While participating in COVID 19 treatments in the research area, the doctor has had a significant  impact on their personal lives and causes job stress.
Keywords: Coronavirus; Doctor; Health Care; Quarantine; Stress